Assessment of Risk Factors in Hypertensive Disorder During Pregnancy: Hospital Based (KAP) Knowledge, Attitude and Practice Survey. A Key for Preventive Approach - Shrestha, Merina (Journal of Nepalgunj Medical College, 2018)
Background: Hypertensive disorder (HDP) during pregnancy is a group of conditions featuring with high blood pressure that may lead to feto-maternal morbidity and mortality, particularly in developing countries.Aims and Objectives: To assess relationship between risk factor of hypertensive disorder during pregnancy, their self care knowledge and practice to prevent and control hypertension.Materials And Method: A cross-sectional study of 93 registered, pregnant women belonging to reproductive ageth group, after 20th  gestation age completed, who came for ANC checkup or admitted for hypertension management or prior to delivery in Nepalgunj medical college and teaching hospital under department of Obstetrics and Gynecology from 15th  June to 15th  December 2018. Blood pressure was measured for each women at booking or at subsequent visits. Urine test for protein albumin was performed if blood pressure was elevated. Data was entered and analysis was completed using SPSS package version 20.Results: The overall prevalence of hypertensive disorder during pregnancy was 2.85% among all deliveries. Pre-eclampsia accounted 36% of the cases followed by eclampsia 18%. Gestational hypertension was 21%, pregnancy induced hypertension was 20% and chronic hypertension was only 5% in study population.Conclusion: Knowledge and attitude regarding lack of exercise, low salt diet, obesity and lack of rest were poor contributory risk factors. It is recommended that all pregnant women must develop knowledge about associated risk factors and ensure the application of behavioral change practices to control and prevent hypertensive disorder during pregnancy.